(untitled) (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
This study aims to evaluate the effectiveness of a teacher training program in improving pedagogic competence at Nurul Ilmi Jambi Integrated Islamic School (SIT). The evaluation is directed at measuring the impact of training on reaction, learning, behavior, and outcomes to provide a comprehensive picture of its contribution to teacher professionalism and educational quality. The study employed the Kirkpatrick Evaluation Model with a qualitative approach. Data were collected through in-depth interviews, classroom observations, and document analysis using interview guidelines, observation sheets, and lesson plan reviews. Data were analyzed thematically with Miles and Huberman’s interactive model, supported by triangulation for validity. Findings show that teachers gave positive responses to training relevance and facilitation, though duration was considered short. Knowledge of differentiated learning improved, but some teachers struggled with its application. Behavioral changes appeared in lesson planning and teaching practices, yet varied in consistency. Student engagement increased, although improvements in learning outcomes were more evident in highly motivated students. This study is applicable to Islamic schools, teacher development initiatives, and professional learning communities. Its originality lies in applying the comprehensive Kirkpatrick Model in the context of Integrated Islamic Schools, offering new insights into linking training activities with sustainable pedagogical transformation.